Phytochemical analysis of Annona atemoya seed extract by HPLC and their ability to inhibit the growth of Agrobacterium tumefaciens - NAJWA IBRAHIM KHALEEL AL-BARHAWEE; WJDAN SALIM QASIM; YOUSRA A. ABDLLA (Society for Indonesian Biodiversity, 2023)
Abstract. Al-Barhawee NIK, Qasim WS, Abdlla YA. 2023. Phytochemical analysis of Annona atemoya seed extract by HPLC and their ability to inhibit the growth of Agrobacterium tumefaciens. Biodiversitas 24: 603-608. The main objective of this study was to determine the effectiveness of Annona atemoya seeds crude alcoholic extract utilizing nine different concentrations (0.0020, 0.0039, 0.0060, 0.0080, and 0.00100 mg/ml). Agrobacterium tumefaciens causes crown gall disease in numerous plant crops causing significant economic losses. Medicinal plants contain chemical compounds (a group of secondary metabolites) known to have antibacterial properties. The result showed that the minimum inhibitory concentration was (0.0313 mg/ml) using agar diffusion technique, while it ranged from (0.0156-0.0313 mg/ml) in the minimal microplate inhibitory concentration test. The crude alcoholic extract of A. atemoya seeds contains alkaloids, flavonoids, glycosides, tannins, phenols, and proteins, but not saponins, based on the results of qualitative analysis of chemical components. HPLC analysis revealed that the extract contained quercitin, rutin, valine, and camphor which were found in the amount of 33.09, 139.39, 0.061, and 7.43 ppm/ml, respectively. Therefore the present finding suggests that A. atemoya seed extract may be used as a biological control to inhibit crown gall formation in plants. This is the first study of the antimicrobial activity of A. atemoya seed alcoholic extract on the growth of plant pathogenic bacteria.